Simultaneous determination of both kavalactone and flavokawain constituents by different single‐marker methods in kava. Issue 14 (25th May 2021) - Zhao, Xiaojun; Su, Chao; Ren, Ruru; Zhang, Bo; Wang, Yingli; Su, Xiaojuan; Lu, Fangfang; Zong, Rong; Yang, Lingling; Zhang, Wannian; Ma, Xueqin
Abstract: Kava, the rhizomes and roots of Piper methysticum Forst, is a popular edible medicinal herb traditionally used to prepare beverages for anxiety reduction. Since the German kava ban has been lifted by the court, the quality evaluation is particularly important for its application, especially the flavokawains which were believed to be responsible for hepatotoxicity. Now, by employing two different standard references and four different methods to calculate the relative correction factors, eight different quantitative analyses of multicomponents by single‐marker methods have been developed for the simultaneous determination of eight major kavalactones and flavokawains in kava. The low standard method difference on quantitative measurement of the compounds among the external standard method and ours confirmed the reliability of the mentioned methods. A radar plot clearly illustrated that the contents of dihydrokavain and kavain were higher, whereas flavokawains A and B were lower in different kava samples. Only one of eight samples did not detect flavokawains that may be related to hepatotoxicity. In summary, by using different agents as an internal standard reference, the developed methods were believed as a powerful analytical tool not only for the qualitative and quantitative of kava constituents but also for the other multicomponents when authentic standard substances were unavailable.